Elementary School Teachers’ Problems in Online Learning during the Pandemic - Erawati, Gusti Ayu Putu Sintha Arma; Widiana, I Wayan; Japa, I Gusti Ngurah (Universitas Pendidikan Ganesha, 2021)
COVID-19 pandemic has caused chaos in various field such as economic, social, tourism and many more. One of the fields that affected to it is in the field of education. The government requires schools in Indonesia to carry out online learning activities from home. This policy certainly raises various problems not only for students but also for teacher, many teachers faced problems during the online learning. This research was conducted to find out the problems experienced by elementary school teachers in online learning during the pandemic. The method of research carried out by the researchers is descriptive research, with a population of 25,524 elementary school teachers in Bali, and the research samples were taken from 994 teachers. The data collection method used is the Guttman Scale questionnaire with quantitative descriptive analysis method. The result of the research shows that teachers experience problems in all dimensions, such as the communication dimension with 65%, the learning method dimension 52%, the assessment dimension 61%, the technology use dimension 43%, the network dimension 52%, the dimensions of the cost of cellular internet data 52% and problems in online learning in 74%. It can be concluded that elementary school teachers faced the problems in all of dimentions such as communication dimension, the learning method dimension, the assessment dimension, the technology use dimension, the network dimension, the dimensions of the cost of cellular internet data also problems in online learning.